Impact of Plasmonic Nanoparticles on Poikilocytosis and Microrheological Properties of Erythrocytes - Tatiana Avsievich; Ruixue Zhu; Alexey P. Popov; Alexander Yatskovskiy; Anton A. Popov; Gleb Tikhonowsky; Andrei I. Pastukhov; Sergei Klimentov; Alexander Bykov; Andrei Kabashin; Igor Meglinski (MDPI AG, 2023)
Plasmonic nanoparticles (NP) possess great potential in photothermal therapy and diagnostics. However, novel NP require a detailed examination for potential toxicity and peculiarities of interaction with cells. Red blood cells (RBC) are important for NP distribution and the development of hybrid RBC-NP delivery systems. This research explored RBC alterations induced by noble (Au and Ag) and nitride-based (TiN and ZrN) laser-synthesized plasmonic NP. Optical tweezers and conventional microscopy modalities indicated the effects arising at non-hemolytic levels, such as RBC poikilocytosis, and alterations in RBC microrheological parameters, elasticity and intercellular interactions. Aggregation and deformability significantly decreased for echinocytes independently of NP type, while for intact RBC, all NP except Ag NP increased the interaction forces but had no effect on RBC deformability. RBC poikilocytosis promoted by NP at concentration 50 <semantics>μ</semantics>g mL<semantics>−1</semantics> was more pronounced for Au and Ag NP, compared to TiN and ZrN NP. Nitride-based NP demonstrated better biocompatibility towards RBC and higher photothermal efficiency than their noble metal counterparts.